Perencanaan strategi dasar online marketing guna memaksimalkan fungsi mobile phone untuk Membangun jiwa enterpreneur Dikalangan mahasiswa Universitas harapan Medan - Samosir, Suhaila Husna; Tumanggor, Mutawaqil Bilah; Dita Deviana Fadhilah (LPPI UMN AL WASHLIYAH, 2024)
Digital marketing-based entrepreneurship is becoming an increasingly interesting topic in the digital era. Various sectors and industries are starting to apply digital technology to increase their efficiency and productivity. Based on the Pre-Survey, the situation experienced by our partners, namely students at Harapan University, Medan, is located at Jl. Imam Bonjol No. 35 Medan, namely that there is still a lack of understanding about the motivation of the entrepreneurial spirit among productive age groups, in this case students. Many students in the current digital era still use it only to access entertainment. In fact, if they know the knowledge and dare to try, it can be used to generate income at a young age (Generation Z). Generation Z is a generation that was born, raised and grew up in a digital environment. A generation that cannot be separated from gadgets and social interaction in cyberspace. Wherever and whenever they will remain online. Mobile phones are currently like two sides of a coin, on the one hand, with the use of mobile phones, everyone can access various information from various parts of the world, but on the other hand, it can make people addicted to the various entertainment offered, especially with social media. Who knows how much time can be spent playing social media.